CYBERSECURITY AND GLOBAL INFORMATION PROTECTION CHALLENGES - Ahronova Suhondon Shodmon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the digital age, cybersecurity has become one of the most pressing global concerns. Rapid technological advancements, widespread internet use, and the increasing sophistication of cyberattacks have exposed individuals, organizations, and governments to significant information security risks. This article explores the key challenges in global information protection, including cybercrime, data breaches, critical infrastructure vulnerability, and privacy violations. It also analyzes strategies, frameworks, and international cooperation efforts to mitigate cyber threats. The study emphasizes the importance of combining technological solutions, policy regulations, and public awareness to achieve effective cybersecurity and safeguard sensitive data in a global context.